1995
DOI: 10.1128/aem.61.6.2314-2321.1995
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic Response of the Extreme Thermoacidophile Metallosphaera sedula to Thermal and Nutritional Stresses

Abstract: The bioenergetic response of the extremely thermoacidophilic archaeon Metallosphaera sedula to thermal and nutritional stresses was examined. Continuous cultures (pH 2.0, 70؇C, and dilution rate of 0.05 h ؊1) in which the levels of Casamino Acids and ferrous iron in growth media were reduced by a step change of 25 to 50% resulted in higher levels of several proteins, including a 62-kDa protein immunologically related to the molecular chaperone designated thermophilic factor 55 in Sulfolobus shibatae (J. D. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Pronounced changes in phylogeny occur in both acidic spring types including appearance of archaeal and bacterial sequences whose close relatives have all been implicated in the oxidation of Fe II . The presence of Metallosphaera, Sulfobacillus, Acidimicrobium and Thiomonas-like sequences in the Fe-oxide mats is generally consistent with possible chemolithotrophy on Fe II using O 2 as an electron acceptor (Peeples & Kelly, 1995;Norris et al, 1996;Bruneel et al, 2003;Johnson et al, 2003). There is also evidence of heterotrophic populations that may reduce Fe III such as sequences related to Acetobacteracaea Y008, an isolate obtained from Norris Basin (Johnson et al, 2003).…”
Section: Microbial Population Distributionmentioning
confidence: 60%
See 1 more Smart Citation
“…Pronounced changes in phylogeny occur in both acidic spring types including appearance of archaeal and bacterial sequences whose close relatives have all been implicated in the oxidation of Fe II . The presence of Metallosphaera, Sulfobacillus, Acidimicrobium and Thiomonas-like sequences in the Fe-oxide mats is generally consistent with possible chemolithotrophy on Fe II using O 2 as an electron acceptor (Peeples & Kelly, 1995;Norris et al, 1996;Bruneel et al, 2003;Johnson et al, 2003). There is also evidence of heterotrophic populations that may reduce Fe III such as sequences related to Acetobacteracaea Y008, an isolate obtained from Norris Basin (Johnson et al, 2003).…”
Section: Microbial Population Distributionmentioning
confidence: 60%
“…When the actual processes and microbial populations are examined, it is clear that Fe II oxidation is very important in the acidic springs, where copious amounts of Fe(OH) 3 phases (and jarosite in RS2) are formed due to microbial processes Macur et al, 2004a) (Fuchs et al, 1995;Peeples & Kelly, 1995;Norris et al, 1996;Bruneel et al, 2003;Johnson et al, 2003). The higher pH springs (JC3 and NGB-PS) clearly show higher free-energy values for Fe 2+ oxidation due to significant decreases in H + activity (Reaction 25), or the lower calculated Fe 3+ activities (Reaction 24) ( Fig.…”
Section: Reactions With Ironmentioning
confidence: 99%
“…3), corresponding to the emergence of band B25, which is 98% similar to the sequence of Metallosphaera prunae. The Metallosphaera genus includes chemolithoautotrophs that are capable of growth on S° or Fe(II) (Fuchs et al, 1995;Peeples & Kelly, 1995). Thus, it appears that the Metallosphaera-like population was involved in HFO mat formation in a warmer region of the spring channel, as opposed to the Thiomonas-like population that was always detected at <56 °C.…”
Section: Formation Of As(v)-hydrous Ferric Oxide Microbial Matsmentioning
confidence: 99%
“…17 and 21, Table 2). The deposition of As(V)rich HFO correlated with the appearance of Thiomonas, Acidimicrobium, and Metallosphaera-like populations whose closest cultivated relatives have been shown to oxidize Fe(II) and/or As(III) (Dennison et al, 2001;Peeples & Kelly, 1995;Bruneel et al, 2003;Johnson et al, 2003). Several potentially important bacterial and archaeal sequences detected in the HFO mat following initial colonization were not closely related to 16S rDNA sequences from previously characterized organisms, and their physiologies are essentially unknown.…”
Section: Microbial Species Distribution and Community Developmentmentioning
confidence: 99%
“…Chaperonins are double‐ring structures found in nearly all organisms and composed of 60 kDa protein subunits referred to as heat shock proteins or HSP60s (Trent, 1996; Hartl and Hayer‐Hartl, 2002). Heat and other stresses cause some organisms to increase the synthesis of their HSP60s, and it has been suggested that the chaperonins they form play essential roles in helping cells to recover from stress‐related damage (Sanders, 1993; Peeples and Kelly, 1995; Trent et al ., 1998). As proteins are damaged by HSP60‐inducing stresses, a role for chaperonins in refolding damaged proteins was proposed (Edington et al ., 1989; Hightower, 1991) and later generalized to include a role for chaperonins in de novo protein folding under non‐stress conditions (for a review, see: Gething, 1997; Hartl and Hayer‐Hartl, 2002).…”
Section: Introductionmentioning
confidence: 99%